2015
DOI: 10.5688/ajpe798116
|View full text |Cite
|
Sign up to set email alerts
|

An Assessment of Service-Learning in 34 US Schools of Pharmacy Follow Up on the 2001 Professional Affairs Committee Report

Abstract: Objective. To determine if the service-learning components used at a convenience sample of schools and colleges of pharmacy meet the intent of the 2001 AACP Professional Affairs Committee (PAC) report.Methods. An online questionnaire was used to survey faculty members or staff involved with servicelearning education at their school of pharmacy. Questions addressed aspects of service-learning including types of activities used, duration of student involvement with community partners, and association of learning… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 21 publications
0
13
0
2
Order By: Relevance
“…As a pragmatic form of experiential education that also supports societal needs, service-learning provides the unique opportunity to address disparities in care while providing a dynamic experiential environment to strengthen student skills. 3 As the pharmacy profession continually progresses toward active involvement in direct patient care, schools of pharmacy have been increasingly incorporating service-learning into curriculums over the past two decades. 4,5 Accrediting agencies such as the Accreditation Council for Pharmacy Education (ACPE) and professional organizations such as the American Association of Colleges of Pharmacy (AACP) recognize the value of service-learning for fostering future pharmacists who serve individual, community, and societal needs, as well as seek justice in the distribution of health resources as outlined in the Code of Ethics for pharmacists.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a pragmatic form of experiential education that also supports societal needs, service-learning provides the unique opportunity to address disparities in care while providing a dynamic experiential environment to strengthen student skills. 3 As the pharmacy profession continually progresses toward active involvement in direct patient care, schools of pharmacy have been increasingly incorporating service-learning into curriculums over the past two decades. 4,5 Accrediting agencies such as the Accreditation Council for Pharmacy Education (ACPE) and professional organizations such as the American Association of Colleges of Pharmacy (AACP) recognize the value of service-learning for fostering future pharmacists who serve individual, community, and societal needs, as well as seek justice in the distribution of health resources as outlined in the Code of Ethics for pharmacists.…”
Section: Introductionmentioning
confidence: 99%
“…6 The benefits of service-learning have gained increased recognition in health care education, specifically with publications in dental medicine, medicine, and nursing education literature. 3 As of 2015, all participants in the 2013-2014 AACP Academic Leadership Fellows program indicated that students in their professional…”
Section: Introductionmentioning
confidence: 99%
“…8 Respondents to a 2014 survey of a convenience sample of pharmacy schools reported that 85.3% of institutions were utilizing service-learning. 9 …”
Section: Background and Purposementioning
confidence: 99%
“…Recent reviews of nursing, occupational therapy and pharmacy education cite this as gaining interest across all years of nursing education and serving to advance learner competency and understanding in: applying class content to careers, communication, team building, role awareness, civic awareness, leadership, determinants of health and personal growth. (Murray 2013, Taylor & Leffers 2016, Yancey 2016, Schlesselman et al 2015 As with most experiential learning planned within a curriculum, the key issue for our course has been patience. There is a fair amount of documentation required as well as dialogue amongst the students, our undergraduate medical education office, and the partner community agencies.…”
Section: Summary Of Workmentioning
confidence: 99%